The impact of COVID‐19 pandemic lockdown on smoking habits and lifestyle: A cross‐sectional study - Almu'atasim Khamees (11875640) (2023)
Background and Aims Throughout the COVID‐19 lockdown, the resultant psychological disturbances led to more tobacco consumption and deteriorated smoking behaviors among smokers. In this study, we aimed to investigate the impact of the COVID‐19 pandemic on the smoking behaviors of the Jordanian population. Methods A cross‐sectional online survey was designed using the Google Forms service and distributed by social media platforms. Responses were collected starting from November 12, 2020, until November 24, 2020. Results A total of 2511 respondents completed the survey, 77.3% were females. Males were significantly smoking more than females (p < 0.0001). Smoking was significantly more common among respondents who were older than 18 years old, married, held master's and PhD degrees, and working in non‐health‐related fields (p < 0.0001). Participants who smoke were more likely to adopt an unhealthy lifestyle during the pandemic. Females who started smoking last year were 2.6‐fold more than males (p< 0.0001). We also noticed that there is a significant relationship between those who started smoking and are <18 years, living in a family consisting of seven members or more, being unemployed, having a diploma or bachelor's degree in a health‐related major, having no chronic illnesses, increasing of daily meals or night meals, almost daily sugar intake, starting to follow social media account concerning physical activity, exercising once or twice a week, and sleeping more hours per day since the beginning of the pandemic (p < 0.01). Conclusion The results of our study showed that the lockdown had a significant impact on people's lifestyles including smoking habits. Most of our sample's smoker participants experienced a change in their smoking level mostly, an increase. While those who had a decrease in their smoking level experienced a somehow healthier lifestyle regarding nutrition and other aspects. Other Information Published in: Health Science Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/hsr2.1392